2018
DOI: 10.3390/w10091189
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of China Sponge City Design: The Case of Lincang Technology Innovation Park

Abstract: China launched the sponge city (SPC) initiative in 2013 to reduce municipal stormwater runoff. The design criteria are mainly the annual comprehensive runoff coefficient (ACRC) regulated in a design guideline. Numerous SPC alternatives with varied low-impact development (LID) measures can be designed to meet the ACRC. Obviously, the optimization of SPC design is significant. This study provides an approach to SPC design optimization that applies an optimized module of SUSTAIN to simulate SPC performance over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Specifically, with the increase of the LID proportion of maximum construction area, green roofs performed better than permeable pavements in reducing runoff volume and peak flow, and permeable pavements performed better in peak reduction than runoff reduction. Compared with the results of Liao et al [7] and Li et al [46], the influence of LID proportion of maximum construction area on hydrological performance was evaluated. Overall, LID facilities performed better in the reduction of runoff volume than peak flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, with the increase of the LID proportion of maximum construction area, green roofs performed better than permeable pavements in reducing runoff volume and peak flow, and permeable pavements performed better in peak reduction than runoff reduction. Compared with the results of Liao et al [7] and Li et al [46], the influence of LID proportion of maximum construction area on hydrological performance was evaluated. Overall, LID facilities performed better in the reduction of runoff volume than peak flow.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5, with the decrease in LID proportion of maximum construction area, permeable pavements gradually performed better than green roofs in peak reduction. Li et al [46] found that permeable pavements with an area of about 0.57 ha performed poorly with regard to the peak flow, but performed well in reducing runoff volume. In this project, permeable pavements performed better in runoff reduction than peak reduction when the LID proportion of maximum construction area was less than 80%.…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…The total construction area is 78,500 m 2 that consists of mixed-use of commercial, residential, and public facilities. Figures 6-8 sourced by the reference article [38]. This project construction finished at the end of July 2016 with four LID techniques to reach the design goals of 80% annual runoff volume reduction and 60% TSS removal, which is in accordance with the requirements of China's Sponge City Guideline.…”
Section: Aggregation Of Principal Component Analysis and Correlation mentioning
confidence: 99%
“…In a case study the Lincang Technology Innovation Park (LCTIP) was simulated by SWMM for various LID applications. The inputs for SWMM such as a local 10-year precipitation and evaporation record and LID set, and calibration was discussed in detail in that paper [38]. Therefore, the present study directly used the simulation results by SWMM for individual LIDs.…”
Section: Valuing and Normalizingmentioning
confidence: 99%
“…The SUSTAIN model was developed by the United States Environmental Protection Agency (US EPA) and it aims to provide decision makers with support in the process of selection and placement of NBS measures, and to optimise the hydrological performance and cost-effectiveness of NBS in the urban watershed (Leslie et al, 2009;Li et al, 2018a). There are several studies that apply SUSTAIN with the attempt to minimise the cost of NBS for both runoff quantity (flow volume, peak flow) and runoff quality (pollutant removal) (Gao et al, 2015;Li et al, 2018c).…”
Section: Optimal Configuration Of Nbsmentioning
confidence: 99%